An Evaluation of Anti-Microbial Properties of Gelatin and Collagen Films Enriched by Aloe Vera and Henna to Build an Organic Band Aid - Bayan Khoshkalam*; Ramin Manaffar; Nooshin Sohrabi; Nabi Khaliliaqdam (Lorestan University of Medical Sciences, 2023)
Today, the idea of ​​using biodegradable polymers which can naturally replace skin shortly before skin repair while also inhibiting the growth of bacteria causing wound infection is of great interest. The purpose of this study was to investigate the possibility of making degradable films using natural compounds, including chicken gelatin and collagen, henna plant extract, and aloe vera gel. Materials and Methods: Aloe vera gel and ethanolic extract of the henna plant were prepared and their antioxidants were studied by DPPH (Diphenylpicrylhydrazyl) free radical-scavenging assay. Then, the antimicrobial properties of henna extract and aloe vera gel were evaluated against Enterococcus faecalis, Escherichia coli, Pseudomonas aeruginosa and Candida albicans using the disk diffusion method along with the minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) tests. To prepare the films, the gelatin and collagen extracted from chicken, along with the ethanolic extract of henna and aloe vera gel, was used. Subsequently, the physicochemical and mechanical properties (elasticity, dissolution potency, and moisture level and microscopy investigation) of the films as well as the antimicrobial properties of films against these microbes were investigated. Results: The results revealed that the anti-microbial effects of henna extract and aloe vera gel alone and in combination with gelatin/collagen matrix varied and had different effects on the tested microbes. Moreover, aloe vera showed stronger antioxidant properties than henna. Conclusion: When synthesizing gelatin/collagen-based biopolymers, plant compounds and extracts can be used to enhance the antioxidant and antibacterial properties and apply organic band aids to help heal wounds and prevent wound infections.